Written News Search Engines and Retrieval Systems of the Databases of Spanish Digital Newspapers. Issue 1 (13th October 2021) - Muñoz‐García, Francisco‐Javier; López‐Hernández, María‐Ángeles; Domínguez‐Delgado, Rubén
ABSTRACT: In light of the dearth of empirical studies of the quality of the databases of Spanish digital newspapers, this paper delves into the issue. Accordingly, the databases of 55 Spanish digital general newspapers were examined for the purpose of determining the quality of their retrospective written news search engines and retrieval systems. The results indicate the following: (1) the vast majority of the databases analysed employ search models based exclusively on a calendar or text box, thus hindering the selective retrieval of information; (b) a large proportion of these databases do not allow users to employ several fields in order to filter and narrow down their searches; and (3) all the online news databases lack search guides and controlled vocabularies or thesauruses. From these finding it is possible to infer that the majority of the databases of the Spanish digital press are, as a rule, rudimentary and inefficient.